In situ double-template fabrication of boron-doped 3D hierarchical porous carbon network as anode materials for Li- and Na-ion batteries - Wang, Dan; Wang, Zhiyuan; Li, Yuan; Dong, Kangze; Shao, Jiahui; Luo, Shaohua; Liu, Yanguo; Qi, Xiwei (Applied surface science, 2019)
[Display omitted] •B-doped porous carbon is successfully fabricated by in-situ double-template method.•The porous carbon benefits the diffusion of ions and transportation of electrons.•The carbon network displays excellent performance as anode for NIBs and LIBs. Porous carbon nanostructures with hetero-atom doping are regarded as a promising anode candidate for rechargeable alkalis ion batteries. Herein, a novel boron-doped 3D hierarchical porous carbon network (B-CN) was prepared via a unique in situ double-template (NaCl and HBO3) method. The as-obtained B-CN with high specific surface area (480 m2 g−1), high-defect B-doping (2.74 at. %) and high volume of hierarchical pores (1.28 cm3/g) exhibits a reversible capacity as high as 200 mAh g−1 at 0.1 A g−1 after 100 cycles and superior rate capability of 189 mAh g−1 at 5 A g−1 for Na-ion batteries. It also exhibits excellent cycling performance (496 mAh g−1 after 100 cycles at 0.1 A g−1) and rate capacity (285 mAh g−1 at 5 A g−1) in Li-ion batteries. The outstanding electrochemical performance of B-CN can be attributed to the large surface area with more active sites produce by B-doping, short ions diffusion length and continuous electrons transport pathway provided by 3D hierarchical porous carbon architecture. Moreover, the surface-dominated redox reaction rendered by our tailored B-doped carbon nanostructures is a promising strategy for developing electrode materials with high rate capability. The convenient synthesis process offers a new tactic in fabricating high performance energy storage device.